An Experimental Investigation of the Congestion Control Used by Skype VoIP - Luca Cicco; Saverio Mascolo; Vittorio Palmisano (Proceedings of the 5th International Conference on Wired/Wireless Internet Communications, 2007)
The explosive growth of VoIP traffic poses a potential challenge to the stability of the Internet that, up to now, has been guaranteed by the TCP congestion control. In this paper, we investigate how Skype behaves in the presence of time-varying available bandwidth in order to discover if some sort of congestion control mechanism is implemented at the application layer to match the network available bandwidth and cope with congestion. We have found that Skype flows are somewhat elastic, i.e. they employ some sort of congestion control when sharing the bandwidth with unresponsive flows, but are inelastic in the presence of classic TCP responsive flows, which provokes extreme unfair use of the available bandwidth in this case. Finally, we have found that when more Skype calls are established on the same link, they are not able to adapt their sending rate to correctly match the available bandwidth, which would confirm the risk of network congestion collapse.